PENGARUH KEPUASAN KERJA DAN BEBAN KERJA TERHADAP TURNOVER KARYAWAN PADA PT. AMARTA MULTI DINAMIKA KOTA GORONTALO - Anggriani Husain; Alif Batu (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2024)
This study aims to determine the influence of Job Satisfaction (X1) and Workload (X2) on Employee Turnover at PT Amarta Multi Dinamika, Gorontalo City.The main data collection is through a list ofstatements that are tested through validity and reliability tests. The analysis method used is the method of path analysis (Path Analysis). The results of the first test show that the variables Job Satisfaction(X1) and Workload (X2) simultaneously have a positive and significant effect on Employee Turnover at PT Amarta Multi Dinamika Gorontalo City, namely 0.460 or 46%. The results of testing the second hypothesis indicate that the Job Satisfaction (X1) partially has a negative and significant effect on Employee Turnoverat PT Amarta Multi Dinamika Gorontalo City, namely-0.283 or -28.3%. The results of the third test show that the Workload variable (X2) partially has a positive and significant effect on Employee Turnover at PT Amarta Multi Dinamika Gorontalo City, namely 0.716 or 71.6%.